Deborah Hart Strober and Gerald S. Strober. Confronting Hate: The Untold Story of the Rabbi Who Stood Up for Human Rights, Racial Justice, and Religious Reconciliation - Soloff, Emily D. (Studies in Christian-Jewish Relations, 2020)
No abstract is available.